Pyrochlore electrocatalysts for efficient alkaline water electrolysis1. Issue 20 (28th May 2015) - Parrondo, Javier; George, Morgan; Capuano, Christopher; Ayers, Katherine E.; Ramani, Vijay
<x xml:space="preserve">Abstract</x> Lead ruthenate pyrochlore showed exceptional OER activity and stability when tested in a solid-state alkaline water electrolyzer.